Reviewer Acknowledgment 2015 - De Angelis, Valerio (J Headache Pain, 2016)
The quality of The Journal of Headache and Pain depends on the qualified and regular collaboration of renowned scientists, who devoted their time to constructively review the submitted articles. We are indebted to the following experts who reviewed papers that completed the peer-reviewing process within the year 2015.